1992
DOI: 10.1007/bf02270965
|View full text |Cite
|
Sign up to set email alerts
|

Alternate reproductive strategies in the California gull

Abstract: SummaryWe analysed 6 years of reproduction data for 176 California gulls (Larus californicus) surviving from 1980 to 1988. Using a statistical model adapted from Rao's (1958) andTucker's (1966) generalized growth curve analysis, we reconstructed the reproductive patterns of gulls aged from 0 to 26 years. Individuals were highly consistent in following one of two patterns of reproduction. In a primary pattern employed by most gulls, individuals skipped breeding less frequently and laid larger clutches as they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Our results further underscore the importance of longitudinal data collection (Pugesek and Wood 1992). Taken together, the results of Hunt and Slack (1989), Chavez-Ramirez (1996), Greer (2010), and our data suggest that crab abundance is highly variable and critical to the survival of the over-wintering Whooping Cranes.…”
Section: Discussionsupporting
confidence: 80%
“…Our results further underscore the importance of longitudinal data collection (Pugesek and Wood 1992). Taken together, the results of Hunt and Slack (1989), Chavez-Ramirez (1996), Greer (2010), and our data suggest that crab abundance is highly variable and critical to the survival of the over-wintering Whooping Cranes.…”
Section: Discussionsupporting
confidence: 80%
“…Evidence indicates that the age-related decline in survival of Bam forth gulls is due to increasing reproductive effort with age (Pugesek & D iem , 1990;Pugesek & W ood, 1992). M ost gulls in the population skip breeding less frequently and lay larger clutches as they get older.…”
Section: Resighting Probabilitymentioning
confidence: 98%
“…Pugesek and W ood (1992) have shown that m ost gulls tend to breed regularly and exert greater effort (e.g. lay larger clutches) at each attem pt com pared to a sm aller group that tends to skip breeding and exert lower effort.…”
Section: Resighting Probabilitymentioning
confidence: 98%
“…The literature provides examples of four kinds of studies permitting inferences about the potential adaptive value of nonbreeding: (1) studies that focus on the estimation and comparison of demographic parameters corresponding to breeders and nonbreeders (e.g., Ainley and DeMaster 1980, Harris and Wanless 1995; our study); (2) studies that aim at evaluating the contribution of nonbreeding and other life history options to lifetime production (Scott 1988, Mills 1989, Newton 1989a, Wooller et al 1989; (3) studies that investigate the relationships between temporal variations of breeding proportions, overall adult survival probability and/or overall breeding success at the population level (Coulson 1984, Aebischer 1986, Aebischer and Wanless 1992, Chastel et al 1993, and (4) a study of reproductive strategies emphasizing differences in the frequency of nonbreeding among individuals (Pugesek and Wood 1992). Comparisons among studies using these different methods are difficult, and different interpretations may arise from these methodological differences.…”
Section: (1984) Wooller Et Al (1989) Aebischer and Wanless (1992)mentioning
confidence: 99%